2012
DOI: 10.1055/s-0032-1323704
|View full text |Cite
|
Sign up to set email alerts
|

HLA-A2 Phenotype may be Protective Against Graves’ Disease but not Against Hashimoto’s Thyroiditis in Caucasians

Abstract: Graves' disease (GD) and Hashimoto's thyroiditis (HT) are the most common autoimmune thyroid diseases (AITDs) affecting up to 5% of the general population. In Caucasians HT has a prevalence of up to 4.60% and GD a prevalence of 1-2%. The aim of this study was to investigate the association between HLA-A2 and the AITDs GD and HT among Caucasians. HLA alleles of 33 patients with GD and 75 patients with HT were determined by serological typing. The frequency of HLA A2 was significantly reduced in GD (p=0.033) but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Class I genes encode for HLA antigens A, B, and C, class II genes encode for α- and β-chains of the heterodimeric HLA class II antigens DR, DP and DQ. Class III genes encode for complement components ( 63 ).…”
Section: The Genetic Linkmentioning
confidence: 99%
“…Class I genes encode for HLA antigens A, B, and C, class II genes encode for α- and β-chains of the heterodimeric HLA class II antigens DR, DP and DQ. Class III genes encode for complement components ( 63 ).…”
Section: The Genetic Linkmentioning
confidence: 99%
“…Furthermore, it was estimated that approximately 58% of patients with HT carried at least one of four HLA class I alleles ( HLA - A*02:07 , B*35:01 , B*40:02 , or B*40:06 ) ( 169 ). Conversely, in Caucasian populations, only a few studies have suggested associations between HLA class I alleles and HT risk ( 171 , 172 ). Hence, it is hypothesized that ethnic differences may play a role in the immunological mechanisms involved in thyrocyte destruction ( 169 ).…”
Section: Autoimmune Thyroid Diseasementioning
confidence: 99%
“…An interaction with a SNP in exon 33 of TG has been postulated, suggesting that HLA-DRβ-Arg74 synergises with the disease-associated TG Trp1980Arg SNP [30]. Interestingly, the association of HLA-DRβ-Arg74 is not unique to GD and it may be acting as a general autoimmunity susceptibility allele [31]. The linkage disequilibrium (LD) between genes at the HLA class I and II loci hinder the identification of independent associations Gene expression and SNP data at this locus currently suggest that association may be due to RNASET2, which is expressed in CD4 + T-helper and CD8 + T cells…”
Section: Reviewmentioning
confidence: 99%